Feasibility and safety of PIPAC combined with additional surgical procedures: PLUS study. Issue 10 (October 2022) - Robella, Manuela; Hubner, Martin; Sgarbura, Olivia; Reymond, Marc; Khomiakov, Vladimir; di Giorgio, Andrea; Bhatt, Aditi; Bakrin, Naoual; Willaert, Wouter; Alyami, Mohammad; Teixeira, Hugo; Kaprin, Andrey; et al.
Abstract: Background: PIPAC (Pressurized IntraPeritoneal Aerosol Chemotherapy) is a minimally invasive approach relying on physical principles for improving intraperitoneal drug delivery, including optimizing the homogeneity of drug distribution through an aerosol. Feasibility and safety of the new approach are now consolidated and data on its effectiveness are continuously increasing. Although any surgical procedure associated with PIPAC had always been discouraged due to the high risk of complications, surgical practice is constantly changing: with growing expertise, more and more surgical teams associate PIPAC with surgery. Methods: PLUS study is part of the retrospective international cohort studies including 10 centers around the world (India, Italy, France, Germany, Belgium, Russia, Saudi Arabia, Switzerland) and 96 cases of combined approaches evaluated through a propensity score analysis. Results: the procedures most frequently associated with PIPAC were not only adhesiolysis, omentectomy, adnexectomy, umbilical/inguinal hernia repairs, but also more demanding procedures such as intestinal resections, gastrectomy, splenectomy, bowel repair/stoma creation. Although the evidence is currently limited, PLUS study demonstrated that PIPAC associated with additional surgical procedures is linked to an increase of surgical time (p < 0.001), length of stay (p < 0.001) and medical complication rate (p < 0.001); the most frequently reported medical complications were mild or moderate in severity, such as abdominal pain, nausea, ileus and hyperthermia. No difference in terms of surgical complications was registered; neither reoperation or postoperative deaths were reported. Conclusions: these results suggest that PIPAC can be safely combined in expert centers with additional surgeries. Widespread change of practice should be discouraged before the results of ongoing prospective studies are available.